The Concept of Emotions in Islamic Counseling: A Thematic Analysis of Fear, Anger, Sadness, and Shame According to the Qur'an and Hadith - Evi Zuhara (International Journal of Counseling and Psychotherapy, 2025)
Objective: Emotions are an important aspect of human life that affect psychological and spiritual well-being. In Islamic counseling, understanding how to manage emotions according to Islamic teachings is expected to help individuals deal with various emotional challenges. Objective: This study aims to identify how Islam teaches the management of these emotions and provide practical guidance for counselors in providing Islamic-based counseling services. Method: The method used is Systematic Literature Review (SLR). The collected data were analysed thematically to explore the understanding of emotion management in Islamic teachings and its relevance in counseling practice. Result: Islam provides clear guidance in managing emotions: fear as a form of submission to Allah, anger that must be controlled through patience and forgiveness, sadness that is accepted with calmness and hope, and shame as a motivator for good behaviour. These concepts provide a strong foundation for a more holistic Islamic counseling approach, which integrates spiritual and psychological aspects in overcoming emotional problems. Conclusion: Emotional management in Islam significantly contributes to a more religion-based counseling approach and can be applied to improve individual well-being. Contribution: The main contribution of this study is as a practical guide for Islamic counselors, as well as introducing an approach that incorporates religious values in dealing with emotional problems. In addition, this study also encourages further development in the field of Islamic psychology, particularly in managing emotions in accordance with religious teachings.